Emergency department impaired adherence to personal protective equipment donning and doffing protocols during the COVID-19 pandemic - Tomer Lamhoot; Noa Ben Shoshan; Hagit Eisenberg; Gilad Fainberg; Mansour Mhiliya; Neta Cohen; Orly Bisker-Kassif; Orly Barak; Carolyn Weiniger; Tali Capua (BMC, 2021)
Abstract Objectives Coronavirus Disease 2019 (COVID-19) is a highly infectious viral pandemic that has claimed the lives of millions. Personal protective equipment (PPE) may reduce the risk of transmission for health care workers (HCWs), especially in the emergency setting. This study aimed to compare the adherence to PPE donning and doffing protocols in the Emergency Department (ED) vs designated COVID-19 wards and score adherence according to the steps in our protocol. Design Prior to managing COVID-19 patients, mandatory PPE training was undertaken for all HCWs. HCWs were observed donning or doffing COVID-19 restricted areas. Setting Donning and doffing was observed in COVID-19 designated Emergency department and compared to COVID-19 positive wards. Participants All HCWs working in the aforementioned wards during the time of observation. Results We observed 107 donning and doffing procedures (30 were observed in the ED). 50% HCWs observed donned PPE correctly and 37% doffed correctly. The ED had a significantly lower mean donning score (ED: 78%, Internal: 95% ICU: 96%, p < 0.001); and a significantly lower mean doffing score (ED: 72%, Internal: 85% ICU: 91%, p = 0.02). Conclusions As hypothesized, HCWs assigned to the designated ED wing made more protocol deviations compared with HCWs positive COVID-19 wards. Time management, acuity, lack of personnel, stress and known COVID-19 status may explain the lesser adherence to donning and doffing protocols. Further studies to assess the correlation between protocol deviations in use of PPE and morbidity as well as improvement implementations are required. Resources should be invested to ensure PPE is properly used.